2009
DOI: 10.1002/jrs.2485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vacuum annealing on graphene

Abstract: The effect of vacuum annealing on the properties of graphene is investigated by using Raman spectroscopy and electrical measurement. Heavy hole doping on graphene with concentration as high as 1.5 × 10 13 cm −2 is observed after vacuum annealing and exposed to an air ambient. This doping is due to the H 2 O and O 2 adsorption on graphene, and graphene is believed to be more active to molecular adsorption after annealing. Such observation calls for special attention in the process of fabricating graphene-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
197
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(213 citation statements)
references
References 29 publications
13
197
3
Order By: Relevance
“…Annealing in forming gas and in vacuum results in the blue shift of the position of all three lines, D, G and 2D. There are two reasons for the blue shift of the Raman peaks after annealing: (i) hole doping caused by enhanced ability to adsorb oxygen and water molecules after vacuum annealing and sample exposure to ambient air 27,29,30 or (ii) compressive stress caused by the difference in the thermal expansion of graphene and substrate, slipping of the graphene film over substrate during heating and pinning of annealed at high T a film during cooling back to room temperature 16,[31][32][33][34][35] . It was shown in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Annealing in forming gas and in vacuum results in the blue shift of the position of all three lines, D, G and 2D. There are two reasons for the blue shift of the Raman peaks after annealing: (i) hole doping caused by enhanced ability to adsorb oxygen and water molecules after vacuum annealing and sample exposure to ambient air 27,29,30 or (ii) compressive stress caused by the difference in the thermal expansion of graphene and substrate, slipping of the graphene film over substrate during heating and pinning of annealed at high T a film during cooling back to room temperature 16,[31][32][33][34][35] . It was shown in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is disagreement in the literature about the effects of annealing on the subject of strain and charge doping. Some research concluded that annealing alters the doping, by dopant transfer from the environment or the substrate, or out-gassing of dopants in doped graphene samples [28,45]. Other papers reported that compressive strain is induced in samples after annealing and that this is a competing explanation for the observed changes [19,27].…”
Section: Discussionmentioning
confidence: 99%
“…These sources are often more problematic due to contamination occurring over large areas, rather than as individually adsorbed molecules. Unlike atmospheric contamination, the impurities deposited during experimental processes are often a) Electronic mail: g.h.wells@durham.ac.uk b) Electronic mail: m.r.c.hunt@durham.ac.uk metallic and bond more strongly to the surface preventing their removal via annealing 14,15 . With contamination of graphene samples occurring due to many different factors, which are often unavoidable, cleaning of graphene is important.…”
Section: Introductionmentioning
confidence: 99%
“…With contamination of graphene samples occurring due to many different factors, which are often unavoidable, cleaning of graphene is important. As a result, many different cleaning methods have been reported including mechanical sweeping with an atomic force microscope (AFM) tip 16,17 , the use of sacrificial metal layers 18 , the application of high currents 19 and high temperature annealing under vacuum 14,15 . Although these methods are appropriate for the removal of small concentrations of impurities they are less suitable for cleaning thicker contaminant layers over larger scales.…”
Section: Introductionmentioning
confidence: 99%